The Impact of Positivity and Gratitude on Employee Productivity - Kakkar, Vanshika (Digital Repository of Theses, 2025)
In today's fast-paced work environments, fostering positive psychological states such as gratitude and positivity has become increasingly relevant to enhancing employee productivity and well-being. This study explores the impact of positivity and gratitude on employee productivity through a multi-method approach, incorporating both quantitative measures and qualitative insights. Drawing on theories of positive psychology, we examine how practices of gratitude and positive reinforcement contribute to improved morale, engagement, and efficiency across diverse organizational settings. We conducted a survey with employees across various sectors to assess the direct and indirect effects of gratitude practices on productivity metrics, such as task completion rates, quality of output, and employee turnover. Findings indicate that cultivating a culture of positivity and gratitude not only improves individual productivity but also promotes a collaborative work environment that enhances overall team performance. This paper will explore the impact of positivity and gratitude on employee productivity through a comprehensive literature review. Key topics will include gratitude parameters, positivity parameters, employee mental health, employee productivity, and the broader concept of thankfulness and its relation to the universe. The subsequent sections will delve into each of these areas, drawing on existing research and theoretical frameworks to provide a thorough understanding of how these emotional states influence workplace dynamics and productivity.